Chunky Graphite in Ferritic Spheroidal Graphite Cast Iron: Formation, Prevention, Characterization, Impact on Properties: An Overview - Baer, Wolfram (International journal of metalcasting, 2020)
Ferritic spheroidal graphite cast iron (SGI) materials have a remarkable technical potential and economic impact in modern industry. These features are closely related to the question of how the cast materials can be produced without structural defects and graphite degenerations such as, for example, chunky graphite. Although the chunky graphite degeneration superficially seems to be well known, its metallurgical background is still controversially discussed, appropriate field-tested nondestructive tools for its quantification in castings are lacking, and the knowledge on its impact on material properties is fairly limited. Addressing this status, the article is providing a current overview on the subject. Existing theories on formation and growth mechanisms of chunky graphite are briefly reviewed. Furthermore, from a metallurgical point of view, causes for the appearance of chunky graphite as well as preventive measures are concisely summarized. Particular attention is paid to the morphology of chunky graphite and how it can be characterized by destructive and nondestructive techniques. Special emphasis was laid on providing a comprehensive overview on the impact of chunky graphite on strength, ductility, fatigue limit, fatigue crack growth rate as well as fracture toughness of ferritic SGI materials based on experimental data. Moreover, conclusions for the assessment of castings affected by chunky graphite are drawn.